The effect of ultrasmall grain sizes on the thermal conductivity of nanocrystalline silicon thin films - Battogtokh Jugdersuren (Nature Portfolio, 2021)
Thermoelectric materials convert heat into electricity and their performance is determined by their figure of merit ZT, which is generally too small in many materials for practical applications. Here, the authors demonstrate that a reduction in grain size for nanocrystalline Si can reduce thermal conductivity and potentially be used as a method to engineer greater ZT in Si for thermoelectric applications.